‘We would be well advised to agree on our own basic principles’: Schreiben as an Agent of Discipline-Building in Writing Studies in Germany, Switzerland, Austria, and Liechtenstein - Scott, Andrea (Journal of Academic Writing, 2017)
Although writing centers in Germany are among the oldest and fastest growing outside of North America, scholarship produced within them remains largely unknown outside national borders due to challenges inherent in translingual research. This article helps remedy this gap by rendering accessible debates in ‘writing studies’ (‘Schreibwissenschaft’) in German-speaking countries, where a number of projects are underway to define the field at this moment of its maturation. By focusing on one such initiative in Germany, Stephanie Dreyfürst and Nadja Sennewald’s edited collection Schreiben: Grundlagentexte zur Theorie, Didaktik und Beratung (Writing: Foundational Texts on Theory, Pedagogy, and Consultations) (2014), I use the monograph as a case study for investigating larger scholarly conversations about the state of writing studies in the region. In doing so, I propose a new genre for transnational research—the translingual review. More thickly descriptive than the book review, the translingual review situates the edited or authored monograph within local disciplinary and institutional contexts. This particular translingual review adopts a comparative framework, examining how German-language scholarship extends Anglo-American research in innovative ways, particularly in its uses of writing process research.